Transport modeling for environmental engineers and scientists - Clark, Mark M. (Hoboken, N.J. : Wiley, 2009)
'Transport Modeling for Environmental Engineers and Scientists, Second Edition, builds on integrated transport courses in chemical engineering curricula, demonstrating the underlying unity of mass and momentum transport processes. It describes how these processes underlie the mechanics common to both pollutant transport and pollution control processes'--Provided by publisher.
Includes bibliographical references and index
Keywords: Environmental chemistry -- Mathematical models; Transport theory -- Mathematical models